Energy recovery modeling of pressure-retarded osmosis systems with membrane modules compatible with high salinity draw streams - Husnain Manzoor (17115649) (2020)
A general framework for pressure-retarded osmosis (PRO) process simulation and optimization has been developed to generate performance frontiers (i.e. Pareto curves with respect to specific energy recovery vs. membrane power density) for a given process flowsheet – providing a basis for unequivocal comparisons to be made between the operability of various candidate membrane modules. This work confines itself to pairings between high-salinity oil-produced water (draw) and seawater (feed), which possess a high potential for osmotic energy recovery. It has been shown that the poor mass transfer behavior of a potential PRO membrane may significantly offset gains that could be realized from a high burst pressure compatible with the treatment of high-salinity draw streams. By applying suitable cost parameters to process optimization results and estimating resultant payback periods, it has been shown that the conventional PRO success criterion, which is based on a power density threshold of 5 W/m2, is not sufficient to guarantee the feasibility of the membrane material in plant-scale operation – in the absence of additional optimization of the PRO process flowsheet. Other Information Published in: Desalination License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.desal.2020.114624